Therapeutic approaches targeting intestinal microflora in inflammatory bowel disease - Andoh, Akira (Baishideng Publishing Group Co., Limited, 2006)
Inflammatory bowel diseases, ulcerative colitis, and Crohn’s disease, are chronic intestinal disorders of unknown etiology in which in genetically susceptible individuals, the mucosal immune system shows an aberrant response towards commensal bacteria. The gastrointestinal tract has developed ingenious mechanisms to coexist with its autologous microflora, but rapidly responds to invading pathogens and then returns to homeostasis with its commensal bacteria after the pathogenic infection is cleared. In case of disruption of this tightly-regulated homeostasis, chronic intestinal inflammation may be induced. Previous studies showed that some commensal bacteria are detrimental while others have either no influence or have a protective action. In addition, each host has a genetically determined response to detrimental and protective bacterial species. These suggest that therapeutic manipulation of imbalance of microflora can influence health and disease. This review focuses on new insights into the role of commensal bacteria in gut health and disease, and presents recent findings in innate and adaptive immune interactions. Therapeutic approaches to modulate balance of intestinal microflora and their potential mechanisms of action are also discussed.